Cloning of an origin of DNA replication of Xenopus laevis. - Watanabe, S (1980)
DNA fragments of Xenopus laevis, the African frog, were cloned in the EcoRI site of the Escherichia coli plasmid pACYC189 and tested for ability to initiate and complete replication of the recombinant plasmid when injected into unfertilized eggs of X. laevis. After measurement of the [3H]-thymidine incorporation per egg for a number of recombinant plasmids, pSW14 and pSW9, which respectively contain a small segment (550 base pairs) and several kilobases of frog DNA, were selected for more extensive analysis. In spite of the small size of the segment in pSW14, it incorporates in 2 hr at least 3 times as much labeled thymidine as either pSW9 or the vector alone. The DNA synthesis in pSW14 was shown to be replication rather than repair synthesis, based on a buoyant density shift of the product when iododeoxyuridine was used for labeling. To determine the number of replications of pSW14, a novel method was employed. Because pSW14 is a head-to-head dimer of the vector with the Xenopus fragment inserted at an EcoRI site, the plasmid has three methylatable sites--two bracketing the Xenopus fragment and one opposite the fragment. By cotransformation of E. coli with pSW14 and pBR322 containing the EcoRI methylase gene, supercoiled pSW14 was methylated and injected into eggs with [3H]thymidine. Disappearance of modified EcoRI sites by semiconservative replication was followed by measuring the sensitivity to EcoRI endonuclease over time. The results showed that about 50% of the labeled, supercoiled DNA recovered from eggs after 4 hr was sensitive to EcoRI digestion, which indicates that most of the DNA that incorporated [3H]thymidine had replicated twice during the 4 hr in the unfertilized eggs of X. laevis. We conclude that pSW14 has a functional origin in the Xenopus DNA segment.